Pair Correlation Influence on Superconductors Josephson Penetration Depth - Poudel, Yadhav; Gupta, Suresh Prasad; Shrestha, Narayan Babu; Yadav, Kishori; Dhobi, Saddam Husain (Program Studi Fisika Universitas Negeri Jakarta, 2024)
The Josephson penetration depth is an essential characteristic of Josephson junctions, serving a role akin to the London penetration depth in bulk superconductors. It originates from the substantial self-magnetic field generated by a strong Josephson supercurrent, influencing the distribution of the gauge invariant phase difference across the junction. This study delves into the intricate relationship between cooper pair correlation and critical temperature in superconductors. To study relationships authors develop theoretical method and observed that critical temperature exhibits a noteworthy decrease with an increase in cooper pair correlation. Specifically, as the level of coherence among electron pairs rises, the material's capacity to maintain the superconducting state at elevated temperatures is enhanced, resulting in an elevated critical temperature. Conversely, regions characterized by lower pair correlation demonstrate a sharp reduction in critical temperature, indicating their heightened susceptibility to changes in correlation levels. This sensitivity is particularly pronounced across junction and penetration depth where cooper pair correlation is diminished. Furthermore, the study reveals an exponential decay trend in critical temperature concerning cooper pair correlation, underscoring the pivotal role played by pair correlation in the superconducting state. Even slight alterations in pair correlation have a substantial impact on the material's ability to exhibit superconductivity. These findings provide valuable insights for the tailored design and optimization of superconducting materials for specific applications. By leveraging the understanding gained from this research, it becomes possible to engineer materials with enhanced superconducting properties. This study not only advances our fundamental comprehension of superconductivity but also offers practical implications for a diverse range of technological applications.